2010
DOI: 10.5194/acp-10-3001-2010
|View full text |Cite
|
Sign up to set email alerts
|

Eta-CMAQ air quality forecasts for O<sub>3</sub> and related species using three different photochemical mechanisms (CB4, CB05, SAPRC-99): comparisons with measurements during the 2004 ICARTT study

Abstract: Abstract.A critical module of air quality models is the photochemical mechanism. In this study, the impact of the three photochemical mechanisms (CB4, CB05, SAPRC-99) on the Eta-Community Multiscale Air Quality (CMAQ) model's forecast performance for O 3 , and its related precursors has been assessed over the eastern United States with observations obtained by aircraft (NOAA P-3 and NASA DC-8) flights, ship and two surface networks (AIRNow and AIRMAP) during the 2004 International Consortium for Atmospheric Re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 26 publications
2
30
1
Order By: Relevance
“…Also, ensure that the chemical mechanism used accounts for PAN photolysis and near-IR HO 2 NO 2 photolysis. Photolysis is the dominant PAN chemical loss process in the upper troposphere, where many have reported PAN overprediction (Pickering et al, 2009;Yu et al, 2010;Fang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Also, ensure that the chemical mechanism used accounts for PAN photolysis and near-IR HO 2 NO 2 photolysis. Photolysis is the dominant PAN chemical loss process in the upper troposphere, where many have reported PAN overprediction (Pickering et al, 2009;Yu et al, 2010;Fang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Predictions on other days also show similar agreement with observed data. Previous studies (Yu et al, 2010(Yu et al, , 2012 comparing model predictions obtained with CBIV and CB05 mechanisms to observed PAN from several field campaigns have also noted that these mechanisms overpredict PAN. Thus, the chemistry in RACM2 has improved the predictions of PAN.…”
Section: Impact On Peroxyacetyl Nitrate (Pan)mentioning
confidence: 99%
“…Some specific experimental (e.g. Cros et al, 2004;Drobinski et al, 2007;Yu et al, 2007Yu et al, , 2010Tang et al, 2011) or case studies (e.g. Emeis et al, 2011;Matthias et al, 2012) using upper-level measurements do exist, but comprehensive tropospheric evaluation and model inter-comparisons over long time periods are missing.…”
Section: Introductionmentioning
confidence: 99%